Consistency of Moderate to Vigorous Physical Activity in Middle School Physical Education. Issue 4 (October 2016) - Gill, Monique; Chan-Golston, Alec M.; Rice, Lindsay N.; Cole, Brian L.; Koniak-Griffin, Deborah; Prelip, Michael L.
Abstract : This study assessed the consistency of moderate to vigorous physical activity (MVPA) in a sample of middle school physical education lessons. Random intercept hierarchical linear regressions were employed to model the relationship between consistency of MVPA and independent variables, including lesson and teacher characteristics. Larger classes spent significantly more time in consistent MVPA in the absence of controlling for teacher characteristics. A significant interaction between class size and teacher experience suggests that experience may play a beneficial role in larger classes, and overall class size does not have to be a barrier to achieving high levels of MVPA.